Improving the Ability to Read the Beginning of Consonant Letters in Grade 1 Elementary School with Cooperative Method of Scramble Game Type - Murtini, Murtini (Universitas Sebelas Maret, 2022)
Improving the ability to read beginnings with consonants in grade 1 elementary school through a cooperative method of scramble game type is one of the many ways that low grade teachers can do in fun learning and increase learning motivation because this activity can be done outside the classroom or in the classroom in groups. Learning in low grades requires activities with a pleasant atmosphere because students are still in the learning stage while playing. Teachers must be able to facilitate students who are subjects in the learning system in Indonesia today. In achieving learning outcomes, not only students are active but teachers must always create new ideas that can motivate students and develop students' curiosity.